2015
DOI: 10.1002/app.42436
|View full text |Cite
|
Sign up to set email alerts
|

Nafion‐115/aromatic poly(etherimide) with isopropylidene groups/imidazole membranes for polymer fuel cells

Abstract: Proton exchange membrane fuel cells (PEMFCs) with Pt/C gas diffusion electrodes and graphite single-serpentine monopolar plates were constructed based on an aromatic poly(etherimide) with isopropylidene groups (PI)/imidazole (Im) and a popular Nafion-115 matrix. The electrochemical properties of PEMFCs were tested at 25 and 608C. The maximum power density of 171 mW/ cm 2 and the maximum current density of 484 mA/cm 2 were detected for Nafion-115/PI membrane. For both constructed PEMFCs the efficiency at 0.6 V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…69 Despite the low HNT content, the higher amount of residue mass for the SPSIm/HNT sample could be attributed to the entrapment of some SPS and Im molecules inside the HNT, which would probably result in a mass transport delay that impeded the escape of the SPSIm volatile components. 27,[69][70][71] The cross-section SEM micrographs for all the membranes are presented in Figure 10. The homogenous and dense membrane did not contain any voids or other defects.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…69 Despite the low HNT content, the higher amount of residue mass for the SPSIm/HNT sample could be attributed to the entrapment of some SPS and Im molecules inside the HNT, which would probably result in a mass transport delay that impeded the escape of the SPSIm volatile components. 27,[69][70][71] The cross-section SEM micrographs for all the membranes are presented in Figure 10. The homogenous and dense membrane did not contain any voids or other defects.…”
Section: Resultsmentioning
confidence: 98%
“…Although no significant changes were observed in the thermal stability of the ternary membrane, the results showed that the onset temperature of SPSIm degradation was slightly lower than that of SPS. In the case of SPSIm/HNT, incorporating HNT could not significantly alter the thermal degradation profile 69 . Despite the low HNT content, the higher amount of residue mass for the SPSIm/HNT sample could be attributed to the entrapment of some SPS and Im molecules inside the HNT, which would probably result in a mass transport delay that impeded the escape of the SPSIm volatile components 27,69–71 …”
Section: Resultsmentioning
confidence: 99%
“…PI has excellent thermal and chemical stability, insulation, and good mechanical properties 36–41 due to its rigid aromatic construction and imide rings. It has been widely used in fields of electrical, aerospace, microelectronic devices, gas separation technology, polymer electrolyte fuel and so on 42–52 . The first flexible organic electroluminescent display (OELD) with indium tin oxide (ITO) as the anode was prepared on PI film substrate 53,54 …”
Section: Introductionmentioning
confidence: 99%
“…It has been widely used in fields of electrical, aerospace, microelectronic devices, gas separation technology, polymer electrolyte fuel and so on. [42][43][44][45][46][47][48][49][50][51][52] The first flexible organic electroluminescent display (OELD) with indium tin oxide (ITO) as the anode was prepared on PI film substrate. 53,54 Kapton™ is one of the most successfully commercialized PI films, first synthesized by Sroog 55 in 1965 with pyromellitic dianhydride (PMDA) and 4,4 0 -diaminodiphenyl ether (ODA).…”
Section: Introductionmentioning
confidence: 99%
“…Because of their large specific surface area, high porosity, and tunable mechanical properties, nanofibers have broad application in many fields, including bioengineered structures, air and water filtration, electronics, drug delivery, fuel cells, biomedical tissue engineering, building materials, and smart clothing . However, nanofibers produced by traditional methods present some problems, including their toxic solvents and low output.…”
Section: Introductionmentioning
confidence: 99%